Tata Kelola Kebijakan Qanun Nomor 13 Tahun 2003 Tentang Maisir (Perjudian) Di Kabupaten Gayo Lues Provinsi Aceh - Muhammad Fikar; Dyah Mutiarin (Journal of Governance and Public Policy, 2014)
The concept of regional autonomy and the views from the historical Aceh considered appropriate to enforce ShariaLaw kaffah. Qanun No.13 of 2003 about Maisir (Gambling) is one of the five existing Qanun in the implementationIslamic Sharia in Aceh, with the aim of preventing all forms of implementation and support for implementing gambling,to implement Islamic Sharia there are three institutions that run(1) Department of Islamic Sharia, (2) Satpol PP andWH, (3) Syariah Court. Bu tthe reality is still going on various forms of gambling. The above considerations, there viewwas conducted in order to see how the Governance Policy Qanun No.13 of 2003 about Maisir (Gambling) in Gayo LuesRegencyof Aceh province and Relationships between Implementing Agencies. The method used in answering thereview using qualitative descriptive method to obtain aclear description of the public participation, LSM in the implementationof Qanun No.13 of 2003 and the relationship between the executing agency. Therefore, the technique incollecting the data that used is observation technique which is observe the objects condition in the field, interview theperformers who involved in implementing Qanun Nomor 13 in 2013 about Maisir (gambling) in regency of GayoLueswith record it in a document.